The impact of seed policy reforms and intellectual property rights on crop productivity in India - Kolady, Deepthi; Spielman, David J.; Cavalieri, Anthony J. (Wiley, 2012)
The growth of private investment in developing‐country agriculture, new advances in the biological sciences, and rapid integration of developing countries into the global trading system has heightened interest in the topic of seed market and intellectual property rights’ (IPRs) policies among public policy‐makers, corporate decision‐makers and other actors in the agricultural sector. But there are still unanswered questions about whether emerging and evolving seed policy reforms and IPR regimes in developing countries will contribute to increasing crop productivity and improving food security. This paper attempts to answer some of these questions by focusing specifically on the case of India, the regional leader in implementing seed policy reforms and IPRs in agriculture. Findings indicate that maize and pearl millet yields grew significantly during the last two decades due partly to the combination of (1) public policies that encouraged private investment in India’s seed industry during the 1980s, and (2) biological IPRs conferred by hybridisation that conveniently married the private sector’s need for appropriability with the nation’s need for productivity growth. Although past lessons are not an indication of future success, this convergence of policy solutions and technology opportunities can be replicated for other crops that are vital to India’s food security.